PERAN CAMAT DALAM PEMBINAAN APARATUR PEMERINTAH DESA DI KECAMATAN NANGA MAHAP KABUPATEN SEKADAU - Edo E.42009065 (FISIP Universitas Tanjungpura Pontianak, 2022)
Writing this essay is to describe and analyze the role of district head in doing development the Apparatus Village Government in Nanga Mahap District Sekadau Regency. This essay title based on concerns raised less effective performance in managing headman of the village administration is indicated as district head of carrying out its functions in building the village head, so in this essay will analyze how the district head undescribed and carry out its work in to develop the Apparatus Village Government. This research uses descriptive qualitative research types. The study was done in several stages, starting with doing research advances (pre survey), making research plan (Proposed Research), perform secondary and primary data acquisition thus doing research in the field (interview or observation), followed by data analysis and continue with manufacturing research report (essay). Research location is in District Nanga Mahap Sekadau Regency. Subjects in this study is the District Head Nanga Mahap, Head of district administration Nanga Mahap, Headman of Nanga Mahap Village, Headman of Landau Kumpai Village, Secretary of Nanga Mahap Village, and Secretary of Landau Kumpai Village. Conclusion of this study is the role of district head in doing development the Apparatus Village Government in Nanga Mahap District Sekadau Regency not optimal. It can be seen from the lack of head of sub role in providing guidance, direction as well as education and training to the village head. Therefore, the researchers hope that the district head Nanga Mahap further improve the developtment to Apparatus Village Government that the purpose of achieving the Government District of Nanga Mahap to create better governance.Keywords: Role district head, Construction, Government Reform Country.